Remote vehicle communication anti-interference design based on multipath channel equalisation suppression. (2018) - Liu, Chunling; Huo, Chunbao; Zeng, Xinfa
In order to improve the quality of remote vehicle communication and reduce communication distortion and error, this paper proposes a remote vehicle communication anti-interference design method based on multipath channel equalisation suppression, and constructs a dynamic channel allocation model for multi-vehicle remote communication. The signal-to-interference ratio of each channel is calculated and the continuous fractional frequency method of vehicle communication signal is used for blind source separation and on this basis, feedback link is added to the output end of the communication signal. The research results show that the method has advantages of good balance performance and vehicle communication code element's output error rate is low, anti-interference ability is strong, and the quality of remote vehicle communication is improved.